Feasibility Analysis of Public Service Mall Development in Sungai Penuh City - Putri, Dina Fathia; Zulherman, Zulherman; Utama, Wahyudi P (Jurnal Talenta Sipil, 2025)
The implementation of sustainable development, as mandated by the global SDGs agenda, should be applied across various sectors, including in the context of urban development. This principle can be realized through efficient development practices, focusing on optimal land use and building efficiency. A Public Service Mall (MPP) of Sungai Penuh City intended to be constructed on an idle government-owned land in the city center. This study aims to evaluate the feasibility of establishing the MPP in Sungai Penuh City legally and physicaly and also providing technological alternatives that could optimize the total asset value. The feasibility assessment from legal and physical perspectives is conducted using the Highest And Best Use (HBU) method. Additionally, a Life Cycle Cost (LCC) analysis is performed to determine the MPP's total asset value, facilitating recommendations for optimal technology. The results indicate that constructing the MPP on idle land is feasible. The LCC analysis also suggests that implementing environmentally friendly technologies, such as Solar Power Plants (PLTS) and Rainwater Harvesting (PAH), could enhance the energy efficiency of the MPP in Sungai Penuh City.